The Effect of Utility Value, Hedonic Value and Social Value on Sustainable Purchase Intentions - Febriyanti, Wahyu Fitri; Irmawati, Irmawati (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Consumers not only consider the functional needs of products, but also other values such as personal enjoyment and social values. This research aims to examine the factors influencing sustained purchasing intention among TikTok users in Solo Raya. Within the framework of Utility Value, Hedonic Value, and Social Value, hypotheses are proposed and tested to comprehend the impact of independent variables on purchasing intention, with the mediating role of customer trust. A quantitative method utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) is employed to analyze data collected through the distribution of closed-ended questionnaires to respondents aged 17-30 who have made purchases via TikTok. The research sample comprises 70 respondents from Solo Raya. This study seeks to provide in-depth insights into consumer behavior in the digital era, specifically focusing on the TikTok platform. Practical implications encompass guidelines for e-commerce practitioners to understand and enhance factors influencing sustained purchasing intention. Additionally, this research contributes to the literature on the influence of values and trust in the context of online purchasing, particularly through social media platforms.